Kerangka Kerja Evaluasi Kesesuaian Implementasi Vendor Managed Inventory - Undariyanto, Wiwis; Bahagia, Senator Nur (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2024)
The aim of this research is Vendor Managed Inventory (VMI) collaborating in the supply chain. Suppliers are responsible for the availability of customer goods. VMI developed in the retail industry, the VMI concept has been used in the logistics industry. The successful application of the VMI concept has become an interesting research topic for academics and practitioners. This research develops a conceptual framework for evaluating the suitability of implementing VMI for a product in a specific company. Method through systematic literature review. The result of the research is a framework for the suitability of VMI implementation. The three dimensions of the product-related framework consist of 12 elements and 39 indicators that can be used for further research.